2012
DOI: 10.4103/0972-124x.99266
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of enamel matrix protein (Emdogain® ) in combination with coronally advanced flap in the treatment of multiple marginal tissue recession: A clinical study

Abstract: Background:Gingival recession resulting in root exposure is a common problem faced by clinicians. This clinical study compared the results obtained by treating gingival recession using enamel matrix derivative (Emdogain gel®) along with coronally positioned flap and coronally positioned flap alone.Materials and Methods:Twenty patients with a total of 46 gingival recession defects, each patient with a minimum of two recession defects, were included in the study. The test group, which consisted of 10 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
1
19
0
1
Order By: Relevance
“…A total of 101 articles 30‐131 with 94 RCTs potentially eligible for inclusion into the pooled estimates were identified in the base of evidence, and their main characteristics (i.e., number and age of participants, interventions, follow‐up period, number of sites exhibiting CRC, MRC [percentage], use of RMAs, randomization, allocation concealment, masking of examiners, completeness of the follow‐up period, and risk of bias) are depicted in Table 2 30‐131 . Seven studies were reported in two articles each, and their data were reported under one study name 37,38,57,58,65,66,83,84,90,91,110,111,115,116 …”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 101 articles 30‐131 with 94 RCTs potentially eligible for inclusion into the pooled estimates were identified in the base of evidence, and their main characteristics (i.e., number and age of participants, interventions, follow‐up period, number of sites exhibiting CRC, MRC [percentage], use of RMAs, randomization, allocation concealment, masking of examiners, completeness of the follow‐up period, and risk of bias) are depicted in Table 2 30‐131 . Seven studies were reported in two articles each, and their data were reported under one study name 37,38,57,58,65,66,83,84,90,91,110,111,115,116 …”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%
“…Of the 94 trials included in Table 2, 52 were included in the following sets of meta‐analyses: 1) ADMG/CM + CAF versus SCTG‐based procedures; 31,66,76,97,102,114 2) ADMG/CM + CAF versus CAF; 57,58,86,125 3) BS + GTR with resorbable membranes (RS) + CAF versus GTR with RS + CAF; 62,63,78,101 4) EMD + CAF versus CAF; 51,53,59,71,94,103,115,116 5) EMD + CAF versus SCTG + CAF; 30,32,90,91 6) GTR with RS + CAF versus CAF; 36,83,84 7) GTR (all types of membrane) + CAF versus SCTG‐based procedures; 35,43,55,74,96,101,107,109,117,122,123,126 8) SCTG‐based procedures versus CAF; 40,41,54,56,80 9) SCTG + CAF versus SCTG (epithelial collar); 44,47 10) SCTG‐based procedures, micro versus macro procedures; 42,46 and 11) SCTG‐based procedures versus FGG 70,100 . All of the comparisons were performed using studies reporting data on single defects, except for one comparison on EMD + CAF versus CAF 53,71 that could also be conducted using data on multiple recessions. Primary analyses were performed based on the follow‐up evaluation at 6 months (or the minimum one available), but secondary analyses were also performed using longer‐term data when these were reported by the individual studies.…”
Section: Summary Of What Other Srs Have Evaluatedmentioning
confidence: 99%
“…Of the 10 excluded trials assessing CAF, seven were RCTs on multiple‐recession type defects, one did not report when sutures were removed (timing of removal), and two presented a follow‐up period >6 months (Table 2). 49–59 …”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐five abstracts 2‐4,7,10‐30 were hand reviewed, and seven full articles 10‐13,16,17,29 were reviewed. Four articles 10‐13 are included in this study.…”
Section: Search Outcomementioning
confidence: 99%